Numerical study on strength optimization of Go-Kart roll-cage using different materials and pipe thickness. (2021) - Srivastava, Jay Prakash; Krishna Chaithanya, B.; Sai Teja, K.; Venugopal, B.; Vineeth, S.; Rajkumar, M.; Khan, Habeeb
Abstract: This paper aims to optimize the Go-Kart rollcage strength using different materials and pipe thickness. Chassis design is done based upon the SAE standards provided in the Go-Kart events. Ergonomics factor is also considered keeping in mind the driver's safety and comfort. Chassis design has been done in CAD software SOLIDWORKS version 2018. Front, Rear and Side impact analysis is carried out for three different materials viz. (AISI 4130, 1018 and 1020) and pipe thickness (0.5, 1.0, 1.2, 1.4, 1.6, 2 mm) using Finite Element (FE) software ANSYS 16.0. Results are analysed in terms of Factor of Safety, Deformation and von-Mises Stress. Based upon the results acquired through FE analysis, cost and weight of the materials, it is concluded that AISI 1020 material with thicknesses of 1.4 mm are well suitable for fabricating Go-Kart roll cage. This investigation will provide fundamental strength optimisation strategy and act as a priori in designing the Go-Kart vehicle.